The Life force facing challenges. (Lincolnwood, Ill. National Textbook Co., 1999)
Presents annotated works of fiction addressing the topic of life challenges and a section of related articles with discussion questions.
Keywords: Readers (Secondary); Life change events -- Problems, exercises, etc; Conduct of life -- Problems, exercises, etc; Readers -- Life change events; Life change events -- Fiction; Readers -- Conduct of life; Conduct of life -- Fiction; Readers